Comparison of short controlled ankle motion boots and barefoot walking on spatiotemporal gait parameters and plantar pressure distribution - Selim Muğrabi; Özlem Feyzioğlu (PLoS ONE, 2025)
Controlled ankle motion (CAM) boots are commonly recommended to protect the foot-ankle complex in reducing loading, continuing ambulation, and maintaining daily activities. However, maintaining a normal and comfortable gait while wearing CAM boots is quite challenging. The added weight of the CAM boot, coupled with reduced ankle work capacity, hinders the full execution of gait parameters, leading to spatiotemporal asymmetry. Different loads on the sole also increase the total mechanical work in the foot. The primary aim of this study was to investigate the impact of short CAM boots on spatiotemporal gait parameters and plantar pressure distribution. Twenty-four healthy participants were recruited for the study. The participants were asked to walk barefoot and wear bilateral short CAM boots at their comfortable speed. Spatiotemporal gait parameters, foot-pressure distribution, and force were evaluated with Zebris FDM-THM-S treadmill system (Zebris Medical GmbH, Germany) under both conditions, the right and left extremities were evaluated independently. One-way Analysis of Variance (ANOVA) was used to compare the spatiotemporal characteristics of the participants. Significant differences were observed between barefoot and CAM boot walking for all parameters(p < 0.05), except walking speed (p > 0.05). Short CAM boots walking showed a notable increase in the forefoot, midfoot, and hindfoot pressure distribution, with the highest rise in the midfoot region (p < 0.05). Short CAM boots cause an increase in pressure of the entire sole, therefore, caution should be taken before recommending this device, particularly in midfoot pathologies.